The design of medical IoT operation information platform using reactive algorithm and e-commerce O2O mode - Shao, Xiuli (Network modeling and analysis in health informatics and bioinformatics (Wien), 2021)
To apply the internet of things (IoT) to the medical operation system of the new era under the e-commerce online to offline (O2O) mode to realize the intelligent management of medical operation, first, the theoretical basis of the medical e-commerce O2O mode is put forward. First, the theoretical basis of O2O mode of medical e-commerce is proposed, and the reactive algorithm in a cloud computing environment is proposed. Based on the reactive algorithm, the medical IoT operation information platform is designed, including technical framework, development platform and operating framework; then, the database is designed, including user information management database, online registration database, parallel diagnosis service database, and electronic medical record database; the local area network (LAN) is used to realize the basic medical services under the management of the IoT by means of online registration simulation; the performance of the platform is tested, and the test index is the concurrent connection number. The proposed platform is applied to three different hospitals (H, R and K). June 2019 and August 2019 are taken as two-time nodes before and after the use of the proposed platform in three hospitals, and the relevant income of each hospital is counted. The results show that under the premise that the amount of resource increase is 60, and the concurrent connection number is 60, it is necessary to wait for 8 s before the system starts to increase the number of connections (resources), indicating that the threshold exerts a great effect on the algorithm. Meanwhile, the reactive algorithm cannot maintain the same rate. It will cause a slight stagnation according to the load state of the system. The total income of H and K hospitals decreases after using the proposed medical IoT operation information platform. However, the medical income and drug income increase, the ratio of drug income to total income increases significantly, and the proportion of K hospital increases about 0.3. The conclusion is that under the medical e-commerce O2O mode, the reactive algorithm proposed can be applied to the design of the medical IoT operation information platform, and the actual performance of the platform meets the expected results.